Analysis of the Role of Sharia Product Innovation and Service Digitalization on Customer Satisfaction and Loyalty in West Java Islamic Banks - Judijanto, Loso; Arisondha, Edy; Arini, Rani Eka (Westscience Press, 2024)
This study examines the influence of Sharia Product Innovation and Service Digitalization on Customer Satisfaction and Customer Loyalty in Islamic banks in West Java. Using a quantitative research approach, data were collected from 230 respondents through a structured survey, with responses measured using a 5-point Likert scale. The analysis was conducted using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) to test the proposed hypotheses. The findings indicate that both Sharia Product Innovation and Service Digitalization significantly enhance Customer Satisfaction, which in turn positively influences Customer Loyalty. While product innovation has a stronger effect on satisfaction, both factors contribute meaningfully to loyalty. Customer Satisfaction serves as a critical mediator in the relationship between these variables and loyalty. The study provides practical insights for Islamic banks seeking to improve customer engagement and retention through innovation and digital service enhancements.